A RESEARCH ON PROLIFICACY OF NEW MEDIA IMPLEMENTATIONS OF HOSPITALS' PR DEPARTMENTS IN TURKEY - (:unkn) unknown (My University, 2016)
The aim of this study is to expose communication activities, image creating and reputation building performances of public relations (PR) departments at the Turkish hospitals in terms of both public relations authorities of those organizations and their customers’ perception. On top of that, this study is also supposed to look into new communication developments and applications, which have been put into practice as PR activities at the hospitals, whether increase PR departments’ efforts to meet and/or exceed quality perception of customers. Thus a research, which consists of two steps, has been realized. In the first phase of the research a survey of 55 questions applied on randomly chosen 1113 customers, who were getting service , at 89 different hospitals from 8 big cities of Turkey including Istanbul, İzmir, Sakarya, Bursa, Izmit, Yalova and Eskisehir, Tekirdag. Secondly, structured face to face interviews have been done with public relations specialists of these hospitals. One of the findings of the research is that increase in customers’ perception of the hospital’s quality services and reputation is associated with the public relations department.

Bu çalışmanın amacı, Türkiye’deki hastanelerin müşterileri ve halkla ilişkiler bölümlerinin yönetici-lerinin bakış açılarından ilgili hastanelerin imaj ve itibar yaratıcı iletişim etkinliklerini ortaya koymaktır. Ay rıca söz konusu hastanelerde iletişim ile ilgili uygulamaya konan yaklaşımları ve halkla ilişkiler aktivi-telerini araştırarak, bu uygulamaların ve çabaların müşterilerin kalite beklentilerini karşılamakta ve hatta geçmekte yeterli olup olmadığını ortaya çıkarmaktır. Bu nedenle iki aşamalı bir araştırma gerçekleştiril-miştir. Birinci aşamada, 55 sorudan oluşan bir anket İstanbul, İzmir, Sakarya, Bursa, İzmit, Yalova, Eskişehir ve Tekirdağ illerinde yer alan, toplam 89 hastanede hizmet almakta olan ve rastgele seçilmiş 1113 müşte-riye uygulanmıştır. İkinci aşamada ise, bu hastanelerin halkla ilişkiler bölümlerinin uzmanları ile yapılan-dırılmış yüzü yüze röportaj yöntemiyle görüşmeler gerçekleştirilmiştir. Araştırmanın bulgulardan birisi, hastanelerin artan kalite ve itibar algısının müşterilerce halkla ilişkiler bölümleriyle ilişkilendirilmesidir.
TÜRKİYE'DEKİ HASTANELERİN HALKLA İLİŞKİLER BÖLÜMLERİNİN YENİ MEDYA UYGULAMALARININ VERİMLİLİĞİ ÜZERİNE BİR ARAŞTIRMA